2019
DOI: 10.1021/jacs.9b12626
|View full text |Cite
|
Sign up to set email alerts
|

Pauli Paramagnetism of Stable Analogues of Pernigraniline Salt Featuring Ladder-Type Constitution

Abstract: Polyaniline derivatives represent one of the most widely used classes of conductive polymers. The fundamentally important electronic properties of pernigraniline salts, the fully oxidized and acid-doped derivatives of polyanilines, however, are still not well-understood due to their poor stability and configurational uncertainty. To address these issues and to synthetically access stable analogues of pernigraniline salts, ladder-type constitution was imparted into a series of model oligomer analogues with rigi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 69 publications
0
28
1
Order By: Relevance
“…14a) to generate an analogue of pernigraniline salt P13c-H. For conventional pernigraniline salt, the iminium bonds are labile under ambient conditions so that the polymer is unstable and cannot be extensively investigated for its intrinsic spin properties, while with a ladder-type constitution, the originally labile iminium linkage is stabilized by the extra strand of bonds. 101 The good stability of P13c-H enables the comprehensive study of its strong open-shell character by EPR spectroscopy and SQUID magnetometry (Fig. 14b).…”
Section: Delocalization Of Polarons/bipolaronsmentioning
confidence: 99%
“…14a) to generate an analogue of pernigraniline salt P13c-H. For conventional pernigraniline salt, the iminium bonds are labile under ambient conditions so that the polymer is unstable and cannot be extensively investigated for its intrinsic spin properties, while with a ladder-type constitution, the originally labile iminium linkage is stabilized by the extra strand of bonds. 101 The good stability of P13c-H enables the comprehensive study of its strong open-shell character by EPR spectroscopy and SQUID magnetometry (Fig. 14b).…”
Section: Delocalization Of Polarons/bipolaronsmentioning
confidence: 99%
“…Compared to the emeraldine salt of conventional PANI, which demonstrated both Pauli paramagnetism and Curie paramagnetism, LPS featured one order of magnitude higher c Pauli value and absence of Curie paramagnetism, corresponding to a signicantly enhanced polaron delocalization range and higher density of states of polarons at the Fermi level. 51 The c Pauli of LPS was also signicantly higher than those measured on shorter oligomeric analogues, 11 suggesting that the longer ladder polymer chains allowed for the extension of polaron delocalization. The aciddoped salt of LEB (LES) was also characterized with EPR and SQUID ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a signicantly higher activation energy is required to break the double-stranded backbones of a ladder polymer, translating to high stability that is important for applications under harsh conditions. [9][10][11] These advantageous features render conjugated ladder polymers promising candidates for next generation organic electronic materials.…”
Section: Introductionmentioning
confidence: 99%
“…This feature usually suggests strong antiferromagnet coupling or temperature-independent paramagnetism (TIP). Due to the relatively low calculated spin density and weak spin-orbit coupling in organic polymers, this phenomenon is usually attributed to TIP 31,32 reveal that the spins in these polymers are highly delocalized. 33,34 In particular, for p(TDPP-BBT), the χ M T and T are slightly deviated from the linear relationship at low temperature (red circle in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that conjugated polymers with rigid backbones are strongly aggregated even in dilute solutions 35,36 . The strong intermolecular interaction will affect spin delocalization 31 . To understand the polymer chain interactions, we performed the temperature-dependent UV-vis absorption spectra of p(TDPP-TQ) and p(TDPP-BBT) (Fig.…”
Section: Resultsmentioning
confidence: 99%